Clinical and etiological meaning of anti-carbamylated protein antibodies in rheumatoid arthritis. Issue 4 (2nd October 2018) - Nakabo, Shuichiro
Abstract: Several autoantibodies against proteins with post-translational modifications have been detected in patients with rheumatoid arthritis (RA) and are called anti-modified protein antibodies (AMPAs). Anti-carbamylated protein antibodies (Anti-CarP Ab) are the second most vigorously researched AMPAs following anti-citrullinated protein/peptide antibodies (ACPA). Anti-CarP Ab and ACPA show cross-reactivity to some extent and frequently co-exist with each other in RA, but are two distinct antibodies. Although the diagnostic efficacy of anti-CarP Ab is inferior to that of ACPA, the diagnostic specificity of RA may improve when used in combination with ACPA and rheumatoid factor. Anti-CarP Ab and ACPA are also useful for identifying patients at high risk of more severe joint destruction and cardiovascular diseases. The high prevalence of the co-existence of both antibodies suggests a common factor in their production, and this is important for the development of RA because both antibodies emerge before the onset of clinical symptoms. Neutrophils may also be crucially involved. It is important to distinguish citrullinated antigens from carbamylated antigens because the methods commonly used to detect the former are now known to be cross-reactive with the latter. Research on anti-CarP Ab will provide novel insights into the pathology and etiology of RA.